Facket och individualiseringen : Om hur universitetsstuderande med en framtid som tjänstemän ser på fackligt medlemskap - Lutström, Anna (2016)
This study aims to investigate how university students with a future as white collar workers look at union membership, and if and how this view can be linked to the thesis of the individualized society. The research questions that the study is based on is: How are university students talking about unions, i.e., what is their knowledge / image of the union and the union's role in the workplace, the advantages and disadvantages of a union membership as perceived by the university students and further on if and how university students' views on union membership can be understood through the thesis of the individualized society and how this in this case takes the expression. The study is based on data collection through focus groups and interviews. The selection of the focus groups was based on snowball selection within the frame of requirements in which the participants are within the ages of 20-30 years and is studying a social science program or an engineering program at Luleå technical university. Data collection took place then in the form of two focus group discussions with students and interviews with a union agent and a student union agent from a trade union within the white collar sector. The collected data is analyzed thematically using framework method The results show that students' view of, and knowledge about, the union and the union's role in the workplace based on the extent of the student's work experience. If the student completely lacks work experience or just have the experience of temporary employment the student is also lacking both knowledge of, and relationship to the union. This is also reflected in the advantages and disadvantages that students see in a union membership as they appreciate the career related benefits the most, while the disadvantages are largely about cost. Many of the ideas that the students have relates to the thesis of the individualized society, mainly by the uncertainty they feel about working life. They see a union membership as a further important choice in the ...